Correlation between clinical outcomes and patients’ satisfaction using tarsoconjunctival - Hughes flap for the reconstruction of eyelid defects - Nina Jovanović; Patricia Reisz-Majić; Sunita Mehic-Fazlić; Selma Terzić; Jasmina Alajbegović Halimić; Admira Dizdarević (Medicinski glasnik, 2022)
Aim: To examine and quantify patients’ satisfaction and correlate with the objective clinical presentation after the treatment and to present a comprehensive literature review on tarsoconjunctival/ Hughes flap technique. Methods: A review of more than 159 peer-review articles and a combined retrospective-prospective two-centres case series of 17 patients who underwent a two-stage modified Hughes flap procedure (2019-2021) to repair a lower eyelid defect caused by epithelial cancer was conducted. All patients were followed up for a minimum of six months. Patient macroscopic evaluation of redness, lid position, retraction, trichiasis, conjunctival overgrowth, tissue inflammation/infection and hypertrophic scarring were obtained, and findings were graded on a scale of 1 to 5 or binary YES/NO scale. Patients’ satisfaction using a Likert-type scale and correlation with the clinical presentation were analysed. Results: Pearson correlation coefficient between patients’ satisfaction and clinical presentation was 0.534. Out of 510 (the highest summed score for patients’ satisfaction), the total score was 479 (93.9%); out of 187 (the highest summed score for clinical presentation), the total score was 162 (86.6%). Although both scores were high, a lower correlation coefficient and the higher satisfaction score can be explained by more realistic expectations in oncological patients compared to cosmetic ones. Conclusion: Hughes flaps provide multiple benefits in the reconstruction of selected patients with large defects, especially when poor wound healing is expected, or when local advancement flaps do not provide tension-free reconstruction. The rate of complications is low and manageable, whereas additional therapy is usually observational or symptomatic.
Keywords: epithelial malignant skin tumour; Likert score; periocular region